One-year report on HB-1199: Colorado Healthy Forests and Vibrant Communities Act of 2009: revolving loan fund - Jahnke, Jeff, author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2010)
The report provides an update on the revolving Forest Business Loan Fund authorized by the Colorado General Assembly in House Bill 09-1199. The 2009 bill increases efforts to address wildfire risk, provides resources to the Colorado State Forest Service to augment technical outreach capabilities, and provides loans and grants for market-based forest treatment solutions to reduce wildfire risk.
Submitted by Colorado State Forest Service.
Keywords: wildfire risk; Colorado; forest-based business; forest business loan fund